Tentative Definitions of Evolution in Relation with Type 2 Diabetes - Cem Turaman (Research Highlights in Disease and Health Research Vol. 2, 2023)
Evolution may be defined in various ways. Evolutionary medicine, as a developing field is adding new definitions such as evolutionary trade-offs and ultimate causes of diseases. Type 2 diabetes constitute a good example to evolutionary explanations of diseases. Selfish brain theory and thrifty genotype hypothesis being some of them. The human body is not designed in a way which functions optimally; it has been evolved with compromises which obligate trade-offs that increase the risk of such diseases as type 2 diabetes.